2017
DOI: 10.1136/bmjopen-2017-016942
|View full text |Cite
|
Sign up to set email alerts
|

What factors are associated with reporting lacking interest in sex and how do these vary by gender? Findings from the third British national survey of sexual attitudes and lifestyles

Abstract: ObjectivesTo investigate factors associated with reporting lacking interest in sex and how these vary by gender.SettingBritish general population.DesignComplex survey analyses of data collected for a cross-sectional probability sample survey, undertaken 2010–2012, specifically logistic regression to calculate age-adjusted OR (AOR) to identify associated factors.Participants4839 men and 6669 women aged 16–74 years who reported ≥1 sexual partner (opposite-sex or same-sex) in the past year for the third National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 52 publications
4
41
1
Order By: Relevance
“…It should mainly target the couples given the impact of their interrelation on one another sexual satisfaction. The rst sexual experiences tend to shape later experiences, particularly for women [60]. The latter should be mainly targeted to understand and voice their sexual needs and rights, and men to be attentive and responsive to theirs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should mainly target the couples given the impact of their interrelation on one another sexual satisfaction. The rst sexual experiences tend to shape later experiences, particularly for women [60]. The latter should be mainly targeted to understand and voice their sexual needs and rights, and men to be attentive and responsive to theirs.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these women were in their thirties and highly educated at marriage but were unable to overcome their sexual inhibition. The lack of sexual competence at the rst sexual intercourse alters women's sexual interest [60]. This speci cally applies to women more than men, which further con rms the contextual aspect of women's sexuality [60].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A study conducted in the general population in the US reported that people with a household contribution of less than 20% had more than two times the risk of being sexually inactive [20]. Lack of a sexual interest is a possible contributing factor to reduced sexual activity among unemployed persons [24]. Another possible reason for sexual inactivity for single/divorced individuals is partner preference.…”
Section: Discussionmentioning
confidence: 99%